Putin on Trial: The Reality of Heads of State Immunity before International Criminal Courts - Aghem Hanson Ekori; Paul S. Masumbe (Polit Journal Scientific Journal of Politics, 2022)
The prosecution of serving heads of state before international criminal courts is still very challenging even though most of these courts do not recognise immunities for international crimes. While the recognition of head of state immunity before national and foreign domestic courts for international crimes is supported by customary international law, the recognition of immunities before international criminal courts is determined by the statute creating the court.. Consequently, while the Rome Statute creating the International Criminal Court (the ICC) does not recognise any form of immunity, the Malabo Protocol creating the African Criminal Court (the ACC) recognised the immunity of senior serving state officials for international crimes. Currently, the ICC is investigating the situation in Ukraine which may lead to the possible arrest of President Putin of Russia and his senior officials for crimes against humanity and war crimes committed when Russia invaded Ukraine. The article argues that prosecuting a serving president like Putin by the ICC may be similar to the Al Bashir case because it will be difficult to arrest and surrender him to the Court and also the fact that Russia is not state party to the Rome Statute. Consequently, the waiving of immunity before an international court is not enough; cooperation by the home state of the offender and other states is needed in matters arrest and surrender to the prosecuting court.